The Election of 1860 : A Campaign Fraught with Consequences - Holt, Michael F. (Michael Fitzgibbon) (Book collections on Project MUSE., 2017)
"Without question, the election of 1860 was the most consequential presidential contest in all of American history. The victory of Republican candidate Abraham Lincoln quickly triggered the secession of seven Deep South states and, after Lincoln took office on March 4, 1861 to the secession of four more states and a horrific four-year-long civil war. No other American presidential election has come close to engendering such a catastrophic outcome. While this election is one of the most well-known, studied, and written about US elections, Michael Holt brings a freshness to his volume by noting that Republicans did not focus on slavery, but primarily ran against the record and especially the corruption of the incumbent administration of James Buchanan. He also points out that the traditional portrayal of the election is one of Lincoln versus Douglas in the northern free states and Bell versus Breckinridge in the southern slave states, but that this view "effaces the nationwide revulsion of non-Democrats at the sleaze they identified with Democratic governance. The demand in 1860 to throw the Democratic rascals out was a national, not a sectional, passion.""--